Reciprocal responses of fibroblasts and melanocytes to α-MSH depending on MC1R polymorphisms - Stanisz, Hedwig (Landes Bioscience, 2011)
The melanocortin 1-receptor (MC1R) exhibits several variants in form of single nucleotide polymorphisms (SNPs) that are known to differentially regulate melanocyte function. However, whether and how MC1R polymorphisms also affect fibroblast function has not been investigated so far. Therefore we measured intracellular cyclic adenosine monophosphate (cAMP) concentrations and cellular proliferation upon stimulation with alpha-melanocyte stimulating hormone (α-MSH) in eight different human fibroblast and melanocyte cell lines with wild type and different MC1R SNPs. We found that fibroblasts, as well as melanocytes, show differences in MC1R function depending on the MC1R genotype. MC1R stimulation with α-MSH in wild type (MC1R(wt)) melanocytes results in an increase of intracellular cAMP and cellular proliferation. In contrast, MC1R(wt) fibroblasts react with a decrease of intracellular cAMP and proliferation. In MC1R polymorphic fibroblasts (R163Q, R151C and V60L) both effects are significantly alleviated. Similar, but inverse effects could be found in MC1R polymorphic melanocytes (R142H and V92M) with a significantly lower cAMP increase and proliferation rate compared to MC1R(wt) melanocytes. Our results indicate that the MC1R displays reciprocal growth responses in melanocytes and fibroblasts, depending on the MC1R genotype. Thus, the MC1R seems to be not solely important for the skin pigmentary system, but also for the fibroblast function, and might influence different processes of the dermal compartment like wound healing, fibrosis and keloid formation.